Cochlear Size Assessment Predicts Scala Tympani Volume and Electrode Insertion Force- Implications in Robotic Assisted Cochlear Implant Surgery - Dhanasingh, Anandhan; Swords, Chloe; Bance, Manohar; Van Rompaey, Vincent; Van de Heyning, Paul (Frontiers in Surgery, 2021)
Objectives: The primary aim was to measure the volume of the scala tympani (ST) and the length of the straight portion of the cochlear basal turn from micro-computed tomography (µCT) images. The secondary aim was to estimate the electrode insertion force based on cochlear size and insertion speed. Both of these objectives have a direct clinical relevance in robotic assisted cochlear implant (CI) surgery. Methods: The ST was segmented in thirty µCT datasets to create a three-dimensional (3D) model and calculate the ST volume. The diameter (A-value), the width (B-value), and the straight portion of the cochlear basal turn (S-value) were measured from the oblique coronal plane. Electrode insertion force was measured in ST models of two different sizes, by inserting FLEX24 (24 mm) and FLEX28 (28 mm) electrode arrays at five different speeds (0.1, 0.5, 1, 2, and 4 mm/sec). Results: The mean A-, B-, and S-values measured from the 30 µCT datasets were 9.0 ± 0.5, 6.7 ± 0.4, and 6.9 mm ± 0.5 respectively. The mean ST volume was 34.2 µl ± 7 (range 23 – 50 µl). The ST volume increased linearly with an increase in A- and B-values (Pearson’s coefficient r= 0.55 and 0.56, respectively). The A-value exhibited linear positive correlation with the B-value and S-value (Pearson’s coefficient r = 0.64 and r = 0.66, respectively). In the smaller of the two ST models, insertion forces were higher across the range of insertion speeds during both array insertions, when compared to the upscaled model. Before the maximum electrode insertion depths, a trend towards lower insertion force for lower insertion speed and vice-versa was observed. Conclusion: It is important to determine pre-operative cochlear size as this seems to have an effect upon electrode insertion forces. Higher insertion forces were seen in a smaller sized ST model across two electrode array lengths, as compared to an upscaled larger model. The ST volume, which cannot be visualized on clinical CT, correlates with clinical cochlear parameters. This enabled the creation of an equation capable of predicting ST volume utilizing A- and B-values, thus enabling pre-operative prediction of ST volume.